Chrpsomva bezziana, The Cause of Myiasis on animal And Human : Problem and Control - April H Wardhana (Indonesian Center for Animal Research and Development, 2006)
Myiasis is an infestation of larvae (Diptera) into the live host tissue of warm-blooded animals including humans . This disease is often found in tropical countries, particularly in the community with low socio-economic level. From many flies causing myiasis, Chrysomya bezziana is medically the most important agent due to its obligate parasite property and causing economies losses . Some myiasis cases on humans and animals in Indonesia are caused by C. bezziana larvae infestation or mixed infestation with Sarcophaga sp . Sulawesi, East Sumba, Lombok, Sumbawa, Papua and Java islands were reported as myiasis endemic areas . Myiasis cases on animals occurred after parturition (vulval myiasis) then is followed by umbilical myiasis on their calf or traumatic wounds, while myiasis on humans are caused by untreated fresh wounds or chronic wounds such as leprosy, diabetes, etc . Besides, nature holes like nose, eyes, ears or mouth are also reported as entry port for those larvae . Clinical signs of myiasis are various and non-specific depends on location of infested part of body, i.e . fever, inflammation, pruritus, headache, vertigo, swelling and hipereosinophilia . There would be serious conditions with secondary infection by bacteria . Myiasis treatment on animals is simpler than humans . Surgical operation is often carried out on infested human part of bodies . Insecticides were used to treat animal myiasis but had raised resistant . Myiasis treatment on humans may be done locally or systemically . Antibiotic broad spectrum or which is suitable with culture and resistance status of bacteria were given for systemic treatment . Chloroform and turpentine with ratio 1 : 4 were used for local treatment . Some of essential oils have also been tested in laboratory as an alternative medicine for both humans and animals myiasis . Key words : Myiasis, human, animal, zoonosis, Chrysomya bezziana